The Effect of Sharia Financial Literacy on Student Preferences for Choosing Sharia Financial Products Case Study of Students of Muhammadiyah Bima University - Heni Kusmawati; Ihwan P. Syamsuddin; Muhammad Rasyad Al Fajar (JURNAL PENDIDIKAN IPS, 2025)
This study aims to analyze student preferences towards the use of Islamic financial products at Muhammadiyah University of Bima. In the era of rapid development of Islamic economics, the understanding and interest of students as the younger generation are very important to encourage the growth of the Islamic financial sector. This study uses a quantitative approach with a survey method involving 60 students as respondents. Data were collected regarding questionnaires that measure Islamic financial literacy and student preferences for Islamic financial products. Data analysis was carried out using validity, rehabilitation and simple linear regression tests. The results of the study showed that all indicators used to measure Islamic financial literacy and student preferences were valid and reliable. Islamic financial literacy has a positive and significant effect on student preferences in using Islamic financial products.